Conscious Teachers for a Sustainable India: Cultivating Holistic Educators for a Thriving Future - Ranjan, Rajeev (Journal of Advanced Research in English & Education; Vol 10 No 1 (2025): Journal of Advanced Research in English and Education, 2025)
This article explores the crucial role of “conscious teachers” in fostering a sustainable future for India. Conscious teachers are defined as educators who possess a deep awareness of their own values, biases, and impact, coupled with a commitment to holistic education that integrates environmental, social, and ethical considerations into all aspects of teaching and learning. In the context of India’s unique developmental challenges and rich cultural heritage, cultivating such teachers is paramount for nurturing responsible citizens who can contribute to a sustainable and equitable society. The article argues that traditional teacher training often lacks a comprehensive focus on sustainability and the development of the inner capacities of educators. This paper outlines ten key areas that need to be addressed within Indian teacher education programmes to cultivate conscious teachers. These areas include fostering self-awareness and mindfulness, integrating sustainability across the curriculum, promoting experiential and community-based learning, developing critical thinking for sustainability challenges, cultivating empathy and interconnectedness, empowering teachers as agents of change, embedding ethical considerations in pedagogy, promoting collaborative learning for sustainability, utilizing indigenous knowledge systems, and advocating for policy support for sustainability education. By addressing these aspects, Indian teacher education can produce educators who are not only knowledgeable but also deeply committed to fostering a sustainable future, thereby contributing to a more resilient and harmonious India.